“Why the Hell Do We Need Electronic Health Records?” - Hackl, W. O.; Hoerbst, A.; Ammenwerth, E. (Methods of Information in Medicine, 2011)
Background: Progress in the medical sciences, together with related technologies, in the past has led to higher specialization and has created a strong need to exchange health information across institutional borders. The concept of electronic health records (EHR) was introduced to fulfill these needs. Remarkably, many EHR introduction projects ran into trouble, not least because they lacked the acceptance of EHR among physicians. Negative emotions, such as anxiety and fear due to a lack of information, may cause change barriers and hamper physicians’ acceptance of such projects.Objectives: The goal of this study was to gain deeper insight into the negative emotions related to the intended implementation of a mandatory national electronic health record system (called ELGA) in Austria among physicians in private practice.Methods: Qualitative, problem-centered interviews were conducted with eight physicians in private practice in the capital region of Tyrol. The methods of qualitative content analysis were used to analyze the data.Results: Three hundred and twenty-eight pas sages in the interviews were selected, annotated, and paraphrased. These passages were assigned to 139 different primary categories. Finally, 18 main categories in the form of statements were derived. They were correlated and a theoretical model was formed to explain the genesis of the detected fears and anxiety related to the ELGA project. The results show that the physicians feel uninformed and snubbed. They fear unknown changes, increased costs, as well as workload and surveillance without obtaining any advantages from using electronic health records in their daily practice.Conclusion: Impartial information campaigns that are tailored to the physicians’ needs and questions as along with a comprehensive cost-benefit analysis could benefit the physicians’ opinion of EHRs.
Keywords: Electronic health record (EHR); organizational innovation; risk management; attitude; qualitative research